MXene / BC / PG-AA dual-network conductive hydrogel, preparation method thereof and application of MXene / BC / PG-AA dual-network conductive hydrogel in flexible sensor

Through the preparation of MXene/BC/PG-AA dual network hydrogel, the problem of insufficient strength and stability of existing conductive hydrogels is solved, and high-strength, flexible and conductive hydrogels are achieved, suitable for wearable Equipment and health monitoring, with high sensitivity and long-term stability.

CN119119513APending Publication Date: 2024-12-13XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411229212.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing conductive hydrogels are insufficient in wearable sensing equipment, making it difficult to accurately detect large deformation and high stress, and have poor signal stability, which cannot meet the actual application needs.

Method used

Using the preparation method of MXene/BC/PG-AA dual network conductive hydrogel, the MXene single-layer nanosheets are combined with bacterial cellulose and propylene glycol acrylic acid system to form a high-strength, flexible and conductive hydrogel, using hydrogen The bonds and coordination bonds achieve uniform dispersion of MXene, enhancing the mechanical properties and sensitivity of the hydrogel.

Benefits of technology

It achieves high sensitivity and rapid response over an extremely wide strain range. The sensor maintains stable output after 2000 cycles, has good fatigue resistance and long-term use stability, and is suitable for wearable devices and health monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119513A_ABST
    Figure CN119119513A_ABST
Patent Text Reader

Abstract

The invention discloses MXene / BC / PG-AA dual-network conductive hydrogel and a preparation method and application thereof in a flexible sensor, and belongs to the technical field of flexible electronic devices.The MXene / BC / PG-AA dual-network conductive hydrogel is prepared by the steps that an initiator and a cross-linking agent are dissolved in a first part of deionized water, after a first stirring reaction, a bacterial cellulose solution is added, after a second stirring reaction, a second stirring reaction is carried out, and then the MXene / BC / PG-AA dual-network conductive hydrogel is obtained; adding a second part of deionized water and an MXene single-layer nanosheet solution, and then adding propylene glycol and an acrylic acid monomer solution; after a third stirring reaction, putting the mixture into a mold, sealing, carrying out a polymerization reaction, cooling to room temperature, and demolding to obtain the MXene / BC / PG-AA double-network conductive hydrogel. The double-network conductive hydrogel with a soft polymer chain and a hydrophilic hard polymer chain which are mutually crosslinked is prepared through a simple one-pot method, and the double-network conductive hydrogel has good toughness, high mechanical strength and stable and excellent conductivity. The flexible strain sensor obtained after packaging is pasted on the skin surface, can accurately track the movement of people, and has great potential application value in the fields of movement monitoring and soft robots.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of flexible electronic devices, and specifically relates to a MXene / BC / PG-AA double network conductive hydrogel and a preparation method thereof and application in flexible sensors. Background Art

[0002] Hydrogel flexible strain sensors are electronic devices inspired by human skin. Such sensors are usually attached to the surface of the human body or other objects to work. Therefore, the hydrogel sensitive layer is required to have high flexibility and strength so that it can adapt to various complex deformations and mechanical stresses while maintaining stable electrical signal output. Sparks et al. prepared a hydrogel with extremely high elasticity based on the interpenetrating network of sodium alginate and polyacrylamide, but the system reduced the crosslinking density of the polyacrylamide network, which aggravated the stress relaxation of the hydrogel in the entire hydrogel system, thereby reducing the strength of the hydrogel in the application. The prepared hydrogel sensor cannot accurately detect large deformations and cannot withstand high stress, making it difficult to meet the requirements of practical use. Zhao et al. prepared a poly(2-acrylamide-2-methylpropane sulfonic acid-co-acrylamide) / bacterial cellulose hydrogel with a special interpenetrating and interlocking network structure. High strength (1.28MPa) is achieved by utilizing the interaction between the amino, amide, sulfonic acid groups on the polymer molecular chain and the polyhydroxyl groups on the bacterial cellulose. However, the high strength of hydrogels is usually accompanied by a low tensile strain rate. At the same time, in application tests, there is weak signal stability and inability to withstand cyclic loads. Better balancing flexibility and strength in the gel is an urgent problem to be solved.

[0003] At the same time, in order to further give DN hydrogels excellent conductive properties, researchers introduced conductive materials such as carbon nanotubes and graphene into the hydrogel system. Among them, MXene, as an emerging two-dimensional transition metal carbide or nitride material, has become a hot topic of research due to its excellent conductive properties and mechanical strength. The rich functional groups such as hydroxyl, oxygen or fluorine on the surface of MXene make it have good dispersibility in hydrogels and compatibility with polymer matrices. When MXene is added to hydrogels as a conductive filler, it can be evenly dispersed and cross-linked with polymer chains, which not only enhances the mechanical strength of the hydrogel, but also improves its durability and stability. Dong et al. proposed a double network hydrogel of MXene / TEMPO bacterial cellulose (TOBC) system. Through solvent replacement, the hydrogel has stable mechanical properties. A large number of hydrogen bonds, dynamic three-dimensional network systems and micelle interactions give the hydrogel excellent mechanical properties (elongation at break of 2800% and fracture strength of 420kPa) and extremely high flexibility. However, the application test process still shows the problem of weak signal stability under multiple cyclic loads and low sensitivity. This shows that excessive stacking of MXene in hydrogel will also affect the mechanical properties and sensitivity of the sensor. Therefore, it is also worth studying how to disperse MXene more evenly in the hydrogel sensitive layer to improve the performance of the sensor.

[0004] The limited strength and stability of existing conductive hydrogels have greatly restricted their practical applications in the field of wearable sensing devices. It is urgent to find a new double-network hydrogel with high flexibility, high strength, high stable conductivity, and excellent strain sensitivity, and apply it to flexible strain sensors to accurately detect various strain signals generated by human activities and meet the actual needs of wearable devices and health monitoring. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a MXene / BC / PG-AA dual-network conductive hydrogel and a preparation method thereof and an application in a flexible sensor, so as to solve the technical problems of limited strength and stability of existing conductive hydrogels.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The invention discloses a preparation method of a MXene / BC / PG-AA double network conductive hydrogel, comprising: dissolving an initiator and a crosslinker in a first portion of deionized water, adding a bacterial cellulose solution after a first stirring reaction, adding a second portion of deionized water and a MXene single-layer nanosheet solution after a second stirring reaction, and then adding propylene glycol and an acrylic acid monomer solution; after a third stirring reaction, placing in a mold, sealing, performing a polymerization reaction, cooling to room temperature, and demolding to obtain a MXene / BC / PG-AA double network conductive hydrogel;

[0008] The bacterial cellulose solution is prepared by adding deionized water into a bacterial cellulose dispersion;

[0009] The MXene single-layer nanosheet solution is prepared by dispersing the MXene single-layer nanosheet into deionized water.

[0010] Preferably, the dosage ratio of initiator: cross-linking agent: bacterial cellulose dispersion: MXene monolayer nanosheet: propylene glycol: acrylic acid monomer solution is (200-400) mg: (15-40) mg: (1.5-3) mL: (15-40) mg: (0.8-1.5) mL: (0.4-2) mL.

[0011] Preferably, the preparation method of the bacterial cellulose solution comprises: adding 0.5 to 1.5 mL of deionized water to 1.5 to 3 mL of a bacterial cellulose dispersion having a concentration of 200 to 800 mg / mL, ultrasonically treating for 0.5 to 2 h until the solution is uniformly mixed, to obtain a bacterial cellulose solution.

[0012] Preferably, the preparation method of the MXene single-layer nanosheet solution comprises: dispersing 15 to 40 mg of MXene single-layer nanosheets into 1 to 2 mL of deionized water, ultrasonically treating for 0.5 to 2 h until uniform dispersion, to obtain a MXene single-layer nanosheet solution; the MXene single-layer nanosheets are prepared from single-layer / few-layer Ti3C2 freeze-dried powder.

[0013] Preferably, the initiator is ammonium persulfate; and the cross-linking agent is N,N'-methylenebisacrylamide.

[0014] Preferably, the conditions for the first stirring reaction are: mechanical stirring at 500-1000 rpm for 30-60 min at 55-65°C.

[0015] Preferably, the second stirring reaction time is 10 to 25 minutes; the third stirring reaction condition is: magnetic stirring at a speed of 600 to 1000 rpm for 10 to 25 minutes.

[0016] Preferably, the polymerization reaction conditions are: polymerization reaction at 55-65° C. for 3-5 hours.

[0017] The present invention also discloses a MXene / BC / PG-AA double network conductive hydrogel prepared by the above preparation method, which maintains GF=0.3-1.28 within a strain range of 5%-620%, and a response time of 100-150ms; the sensitive performance maintains stable output after 2000 cycles, the tensile stress is 44.66-45.52kPa, the tensile strength is 152-185kPa; and the elongation at break is 720%-862%.

[0018] The present invention also discloses the application of the MXene / BC / PG-AA double network conductive hydrogel prepared by the preparation method in a flexible sensor.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention discloses a method for preparing a MXene / BC / PG-AA double network conductive hydrogel. In order to prepare a MXene / BC / PG-AA double network conductive hydrogel with good flexibility and high strength required for a flexible strain sensor with excellent performance, the present invention adopts a one-pot method to use a bacterial cellulose (BC) nanostructure with excellent mechanical properties and a single-layer MXene nanosheet as the rigid first network skeleton of the hydrogel to improve its mechanical properties. The polyacrylic acid obtained by introducing propylene glycol (PG) into the free radical polymerization of acrylic acid (AA) is used as the flexible second network matrix of the hydrogel, and a large number of hydroxyl groups therein are cross-linked with water molecules to greatly enhance the flexibility of the hydrogel. In addition, the BC in the rigid network and the AA segments in the flexible network can form stable hydrogen bonds to enhance the network. The functional groups (carboxyl, hydroxyl and carbonyl, etc.) on the surface of the monolayer Ti3C2 MXene nanosheet form hydrogen bonds and coordination bonds with the hydroxyl functional groups on the surface of the BC long fiber microstructure, ensuring that they are evenly dispersed in the rigid network to form a stable conductive system, so that the hydrogel has good conductivity. When the sensor is subjected to strain, the deformation of the matrix causes the MXene nanosheets to slip, thereby greatly improving the sensitivity of the hydrogel sensor. In addition, it interacts with the flexible matrix network through hydrogen bonds, which can further improve the mechanical properties of the hydrogel. In summary, the MXene / BC / PG-AA double-network conductive hydrogel composed of cross-linked "soft" polymer chains and hydrophilic "hard" polymer chains prepared by a simple one-pot method has good toughness, high mechanical strength, and stable and excellent conductive properties. The flexible strain sensor obtained after encapsulating the hydrogel and pasting it on the skin surface can accurately track human movements, showing that it has great potential application value in the fields of motion monitoring and soft robots.

[0021] Furthermore, the preparation method of the bacterial cellulose solution includes: adding 0.5 to 1.5 mL of deionized water to 1.5 to 3 mL of a bacterial cellulose dispersion having a concentration of 200 to 800 mg / mL, ultrasonically treating for 0.5 to 2 hours until the solution is evenly mixed to obtain a bacterial cellulose solution; adding deionized water to the bacterial cellulose dispersion, the viscosity of the water is relatively low, which is conducive to the dissipation of heat during the polymerization process, making it easy to control the temperature of the reaction system. This helps prevent the degradation of the hydrogel performance due to excessive local temperature; in the cross-linking reaction, the water molecules interact with the hydrophilic groups on the polymer chain, which helps to form a three-dimensional network structure of the hydrogel. This structure gives the hydrogel excellent water absorption and water retention properties.

[0022] The present invention also discloses a MXene / BC / PG-AA double network conductive hydrogel prepared by the above preparation method. The MXene / BC / PG-AA double network conductive hydrogel is a high-strength, high-stable conductive double network (DN) hydrogel with soft and hard skeletons and a three-dimensional dense honeycomb lattice network structure; polyacrylic acid obtained by free radical polymerization of acrylic acid (AA) introduced into propylene glycol (PG) is used as the flexible second network matrix of the hydrogel, and a large number of hydroxyl groups therein are cross-linked with water molecules to greatly enhance the flexibility of the hydrogel; the functional groups (carboxyl, hydroxyl and carbon group, etc.) on the surface of the single-layer Ti3C2 MXene nanosheets form hydrogen bonds and coordination bonds with the hydroxyl functional groups on the surface of the BC long fiber microstructure, ensuring that they are evenly dispersed in the rigid network to form a stable conductive system, so that the hydrogel sensor has stable sensor characteristics. The reversible cross-linking synergy between the rigid bacterial cellulose (BC) chains uniformly dispersed in the supporting monolayer Ti3C2 MXene nanosheets and the flexible acrylic acid (AA) chains doped with propylene glycol (PG) gives the hydrogel high mechanical strength and elongation at break (862%). The prepared hydrogel exhibits excellent strain sensitivity, and can maintain high sensitivity (GF = 0.3 ~ 1.28) in an extremely wide strain range (5%-620%), rapid response (100 ~ 150ms) and super stability (stable output after 2000 cycles). Flexible strain sensors based on hydrogels can accurately detect various strain signals generated by human activities and are expected to be used in wearable devices and health monitoring.

[0023] The present invention also discloses the application of the MXene / BC / PG-AA double network conductive hydrogel prepared by the above preparation method in a flexible sensor. When the MXene / BC / PG-AA double network conductive hydrogel is used as a flexible sensor substrate, it can withstand large deformation without breaking, thereby ensuring the stability and durability of the sensor. Under the action of strain, the sensitivity can be greatly improved by the position slip of the MXene nanosheets, thereby realizing the accurate perception of small strains. It can capture and respond to human body movements of various amplitudes, from subtle gestures to large-scale limb movements, and can achieve accurate monitoring. It has good anti-fatigue performance and long-term use stability, which is crucial for wearable devices that need to be worn for a long time and continuous health monitoring applications. It can provide a comfortable wearing experience while ensuring close contact between the sensor and the skin, thereby improving the accuracy of monitoring. It shows great application potential in the fields of motion monitoring, soft robots, human-computer interaction, rehabilitation medicine, and personalized health monitoring, and is expected to promote the further development of flexible sensor technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a flow chart for preparing the MXene / BC / PG-AA conductive hydrogel disclosed in the present invention;

[0025] Figure 2 The optical performance test diagrams of various hydrogels disclosed in the present invention; wherein, (a) is a molding mechanism diagram of MXene / BC / PG-AA hydrogel; (b) is a SEM image of the brittle fracture surface of MXene / BC / PG-AA hydrogel; (c) is a Cryo-EM image of the brittle fracture surface of MXene / BC / PG-AA hydrogel; (d) is an XRD diagram of BC, monolayer MXene, BC / PG and MXene / BC / PG-AA hydrogels; (e) is an FTIR spectrum diagram of MXene / BC-AA, BC / PG-AA and MXene / BC / PG-AA hydrogels;

[0026] Figure 3 Figures showing the mechanical properties of the hydrogels disclosed in the present invention; wherein (a) is the stretching and weight-bearing test of MXene / BC / PG-AA hydrogel; (b) is the tensile fracture stress-strain curve of hydrogels with different components; (c) is the stress-strain curve of the tensile fracture of MXene / BC / PG-AA hydrogels with different BC contents; (d) is the tensile fracture stress-strain curve of MXene / BC / PG-AA hydrogels with different AA substrate contents; (e) is the stress-strain curve of MXene / BC / PG-AA hydrogels at 300% strain for ten cycles; (f) is the stress test of MXene / BC / PG-AA hydrogels at 1000 stretching cycles;

[0027] Figure 4 The electrical performance test diagrams of various hydrogels disclosed in the present invention; wherein, (a) is a schematic diagram of the sensor resistance signal generated by the MXene / BC / PG-AA hydrogel in the circuit; (b) is the conductivity of the MXene / BC / PG-AA hydrogel with different MXene component concentrations; (c) is the change of the resistance strain rate of the MXene / BC / PG-AA hydrogel with the tensile strain; (d) is the response time of the sensor of the MXene / BC / PG-AA hydrogel; (e) is the resistance strain rate of the MXene / BC / PG-AA hydrogel during cyclic tensile strain; (f) is the initial resistance of the MXene / BC / PG-AA hydrogel sensor prepared by the present invention at 20°C to 100°C;

[0028] Figure 5 A comparison chart of the comprehensive performance of the MXene / BC / PG-AA hydrogel sensor prepared in the present invention and the sensors in various references;

[0029] Figure 6 A fast-responding, skin-adhesive flexible strain sensor assembled from the MXene / BC / PG-AA hydrogel disclosed in the present invention is used for monitoring a wide range of human motion; wherein (a) is for detecting finger deformation at different bending angles; (b) is for bending the wrist up and down; (c) is for the bulge of the triceps muscle; (d) is for frowning; and (e) is for swallowing. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0031] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0032] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0033] The MXene / BC / PG-AA dual-network conductive hydrogel disclosed in the present invention has the following advantages: 1. A high-strength, high-stable conductive dual-network (DN) hydrogel with soft and hard skeletons and a three-dimensional dense honeycomb lattice network structure prepared by a one-pot method is proposed; 2. The polyacrylic acid obtained by the free radical polymerization of propylene glycol (PG) introduced into acrylic acid (AA) is used as the flexible second network matrix of the hydrogel, and a large number of hydroxyl groups therein are cross-linked with water molecules, which greatly enhances the flexibility of the hydrogel; 3. The functional groups (carboxyl, hydroxyl and carbon group, etc.) on the surface of the monolayer Ti3C2 MXene nanosheets form hydrogen bonds and coordination bonds with the hydroxyl functional groups on the surface of the BC long fiber microstructure, ensuring that they are evenly dispersed in the rigid network to form a stable conductive system, so that the hydrogel sensor has stable sensor characteristics.

[0034] The preparation method of the MXene / BC / PG-AA double network conductive hydrogel disclosed in the present invention comprises: dissolving 200-400 mg of initiator ammonium persulfate (APS) and 15-40 mg of cross-linking agent N,N'-methylenebisacrylamide (MBAA) in 20-40 mL of deionized water, and mechanically stirring at a speed of 500-1000 rpm for 30-60 min at 55-65° C. to obtain a mixed solution of the initiator and the cross-linking agent; adding 0.5-1.5 mL of deionized water to 1.5-3 mL of bacterial cellulose (BC) dispersion with a concentration of 200-800 mg / mL, and ultrasonically treating for 0.5-2 h until the solution is uniformly mixed; dispersing 15-40 mg of MXene single-layer nanosheets in 1-2 mL of deionized water, and ultrasonically treating for 0.5-2 h until the dispersion is uniform. After mixing the above-mentioned initiator with the crosslinker and BC solution, stir magnetically for 10 to 25 minutes, then add 0.8 to 1.5 mL of deionized water and 0.5 mL of MXene single-layer nanosheet solution, and finally drop 0.8 to 1.5 mL of propylene glycol (PG) and 0.4 to 2 mL of acrylic acid (AA) monomer solution. The obtained mixed solution was magnetically stirred at a speed of 600 to 1000 rpm in an ice water bath for 10 to 25 minutes. Use a syringe to extract 6 mL of the evenly stirred solution and inject it into a homemade vacuum acrylic molding mold (the upper and lower plates are high-temperature resistant acrylic plates, and the middle is a high-temperature resistant molding silicone plate), seal it and move it into a vacuum drying oven, and polymerize it at 55 to 65 ° C for 3 to 5 hours. After cooling to room temperature, demolding can obtain MXene / BC / PG-AA double network conductive hydrogel.

[0035] The MXene / BC / PG-AA double network conductive hydrogel prepared by the present invention maintains high sensitivity (GF=0.3-1.28), rapid response (100-150ms) and super stability (the sensitive performance still maintains stable output after 2000 cycles and the tensile stress can be maintained at 44.66-45.52kPa) in an extremely wide strain range (5%-620%), the tensile strength is 152-185kPa; the elongation at break is 720%-862%.

[0036] The present invention also discloses the application of the MXene / BC / PG-AA double network conductive hydrogel prepared by the above preparation method in a flexible sensor. When the MXene / BC / PG-AA double network conductive hydrogel is used as a flexible sensor substrate, it can withstand large deformation without breaking, thereby ensuring the stability and durability of the sensor.

[0037] Bacterial cellulose dispersion (BC ≥ 95%) was purchased from Guilin Qihong Technology Co., Ltd.; single-layer / few-layer Ti3C2 freeze-dried powder, i.e., MXene single-layer nanosheets (purity 95%), was purchased from Jilin Yiyi Technology Co., Ltd.; N,N-methylenebisacrylamide (MBAA, 99.7%) and ammonium persulfate (APS, 99.7%) were purchased from Shanghai McLean Biochemical Technology Co., Ltd.; acrylic acid (AA, > 98%) was purchased from Shanghai Dingsheng Biotechnology Co., Ltd.; propylene glycol (PG, 99.9%) was purchased from Dow; deionized water (H2O, resistivity 18.2 MΩ) was purchased from Shuyang Kehong Trading Co., Ltd.; silicone rubber (ECOFLEX1 00-30, Smooth-On), copper wire and release film, all chemicals were used as is.

[0038] When encapsulating the sensor, the prepared MXene / BC / PG-AA dual network conductive hydrogel sensitive layer was trimmed to a size of 30mm×10mm×2mm, and the DuPont wire was inserted into the terminal of the MXene / BC / PG-AA dual network conductive hydrogel, and a small section of each wire (excluding the area where the wire was directly inserted) was adhered and firmly fixed to both ends of the hydrogel using Ecoflex flexible material, thereby ensuring the stability of the DuPont wire as an electrode and preventing it from accidentally falling off. In order to prevent the sensor surface from being contaminated by external impurities when not in use, PET films were laminated on both the upper and lower surfaces of the sensor, and then peeled off before the sensor was connected to the surface of the object being measured.

[0039] Example 1

[0040] A method for preparing a MXene / BC / PG-AA double network conductive hydrogel, comprising:

[0041] 250 mg of initiator APS and 20 mg of cross-linker MBAA were dissolved in 30 mL of deionized water, and mechanically stirred at 600 rpm for 30 min at 60 ° C to obtain a mixed solution of initiator and cross-linker. 0.5 mL of deionized water was added to 2 mL of BC dispersion and ultrasonically treated for 1 h until the solution was uniformly mixed to obtain a bacterial cellulose solution. 40 mg of MXene monolayer nanosheets were dispersed in 1.5 mL of deionized water and ultrasonically treated for 1 h until the dispersion was uniform to obtain a MXene monolayer nanosheet solution. The mixed solution of the above-mentioned initiator and cross-linker and the bacterial cellulose solution were mixed and magnetically stirred for 10 to 25 min, and then 1 mL of deionized water and 0.5 mL of MXene monolayer nanosheet solution were added thereto, and finally 1 mL of PG and 2 mL of AA monomer solution were dropped. The obtained mixed solution was magnetically stirred at 800 rpm for 20 min in an ice water bath. 6 mL of the stirred solution was drawn with a syringe and injected into a homemade vacuum acrylic molding mold. After sealing, it was moved into a vacuum drying oven and polymerized at 60°C for 4 hours. After cooling to room temperature, the mold was demolded to obtain a MXene / BC / PG-AA double network conductive hydrogel.

[0042] Example 2

[0043] A method for preparing a MXene / BC / PG-AA double network conductive hydrogel, comprising:

[0044] 200 mg of initiator APS and 15 mg of cross-linker MBAA were dissolved in 20 mL of deionized water, and mechanically stirred at 500 rpm for 30 min at 55 ° C to obtain a mixed solution of initiator and cross-linker. 0.5 mL of deionized water was added to 1.5 mL of BC dispersion and ultrasonically treated for 0.5 h until the solution was uniformly mixed to obtain a bacterial cellulose solution. 15 mg of MXene monolayer nanosheets were dispersed in 1 mL of deionized water and ultrasonically treated for 0.5 h until the dispersion was uniform to obtain a MXene monolayer nanosheet solution. The mixed solution of the above-mentioned initiator and cross-linker and the bacterial cellulose solution were mixed and magnetically stirred for 10 min, and then 0.8 mL of deionized water and 0.5 mL of MXene monolayer nanosheet solution were added thereto, and finally 0.8 mL of PG and 0.4 mL of AA monomer solution were dropped. The obtained mixed solution was magnetically stirred at 600 rpm for 10 min in an ice water bath. 6 mL of the stirred solution was drawn with a syringe and injected into a homemade vacuum acrylic molding mold. After sealing, it was moved into a vacuum drying oven and polymerized at 55°C for 3 hours. After cooling to room temperature, the mold was demolded to obtain a MXene / BC / PG-AA double network conductive hydrogel.

[0045] Example 3

[0046] A method for preparing a MXene / BC / PG-AA double network conductive hydrogel, comprising:

[0047] 300 mg of initiator APS and 25 mg of cross-linker MBAA were dissolved in 30 mL of deionized water, and mechanically stirred at 700 rpm for 40 min at 60 ° C to obtain a mixed solution of initiator and cross-linker. 1 mL of deionized water was added to 2 mL of BC dispersion and ultrasonically treated for 1 h until the solution was uniformly mixed to obtain a bacterial cellulose solution. 25 mg of MXene monolayer nanosheets were dispersed in 1.5 mL of deionized water and ultrasonically treated for 1 h until the dispersion was uniform to obtain a MXene monolayer nanosheet solution. The mixed solution of the above-mentioned initiator and cross-linker was mixed with the bacterial cellulose solution and magnetically stirred for 15 min, and then 1 mL of deionized water and 0.5 mL of MXene monolayer nanosheet solution were added thereto, and finally 1 mL of PG and 1 mL of AA monomer solution were dropped. The obtained mixed solution was magnetically stirred at 800 rpm for 15 min in an ice water bath. 6 mL of the stirred solution was drawn with a syringe and injected into a homemade vacuum acrylic molding mold. After sealing, it was moved into a vacuum drying oven and polymerized at 60°C for 4 hours. After cooling to room temperature, the mold was demolded to obtain a MXene / BC / PG-AA double network conductive hydrogel.

[0048] Example 4

[0049] A method for preparing a MXene / BC / PG-AA double network conductive hydrogel, comprising:

[0050] 350 mg of initiator APS and 30 mg of cross-linker MBAA were dissolved in 35 mL of deionized water, and mechanically stirred at 900 rpm for 50 min at 60 ° C to obtain a mixed solution of initiator and cross-linker. 1.25 mL of deionized water was added to 2.5 mL of BC dispersion and ultrasonically treated for 1.75 h until the solution was uniformly mixed to obtain a bacterial cellulose solution. 30 mg of MXene monolayer nanosheets were dispersed in 1.75 mL of deionized water and ultrasonically treated for 1.5 h until the dispersion was uniform to obtain a MXene monolayer nanosheet solution. The mixed solution of the above-mentioned initiator and cross-linker and the bacterial cellulose solution were mixed and magnetically stirred for 20 min, and then 1.25 mL of deionized water and 0.5 mL of MXene monolayer nanosheet solution were added thereto, and finally 1.25 mL of PG and 1.5 mL of AA monomer solution were dropped. The obtained mixed solution was magnetically stirred at 900 rpm for 20 min in an ice water bath. 6 mL of the stirred solution was drawn with a syringe and injected into a homemade vacuum acrylic molding mold. After sealing, it was moved into a vacuum drying oven and polymerized at 60°C for 4.5 hours. After cooling to room temperature, the mold was demolded to obtain a MXene / BC / PG-AA double network conductive hydrogel.

[0051] Example 5

[0052] A method for preparing a MXene / BC / PG-AA double network conductive hydrogel, comprising:

[0053] 400 mg of initiator APS and 40 mg of cross-linker MBAA were dissolved in 40 mL of deionized water, and mechanically stirred at 1000 rpm for 60 min at 65 ° C to obtain a mixed solution of initiator and cross-linker. 1.5 mL of deionized water was added to 3 mL of BC dispersion and ultrasonically treated for 2 h until the solution was uniformly mixed to obtain a bacterial cellulose solution. 40 mg of MXene monolayer nanosheets were dispersed in 2 mL of deionized water and ultrasonically treated for 2 h until the dispersion was uniform to obtain a MXene monolayer nanosheet solution. The mixed solution of the above-mentioned initiator and cross-linker was mixed with the bacterial cellulose solution and magnetically stirred for 25 min, and then 1.5 mL of deionized water and 0.5 mL of MXene monolayer nanosheet solution were added thereto, and finally 1.5 mL of PG and 2 mL of AA monomer solution were dropped. The obtained mixed solution was magnetically stirred at 1000 rpm for 25 min in an ice water bath. 6 mL of the stirred solution was drawn with a syringe and injected into a homemade vacuum acrylic molding mold. After sealing, it was moved into a vacuum drying oven and polymerized at 65°C for 5 h. After cooling to room temperature, the mold was demolded to obtain a MXene / BC / PG-AA double network conductive hydrogel.

[0054] Table 1 The amount of each component used in the preparation of hydrogels with different components

[0055]

[0056] Table 2 Amount of components used in the preparation of MXene / BC / PG-AA hydrogels with different BC contents

[0057]

[0058] Table 3 Amounts of components used in the preparation of MXene / BC / PG-AA hydrogels with different AA substrate contents

[0059]

[0060] See Table 1 for a control group of hydrogels with different components; as can be seen from the table, the components are different. After the introduction of the BC rigid skeleton, the tensile strength of the hydrogel was greatly improved, from 55kPa to 185kPa. After the introduction of PG, although the tensile strength of the hydrogel was slightly reduced (152kPa), its elongation at break was further increased to 862%. This shows that by adding BC and PG to the hydrogel, its tensile strength and elongation at break can be increased respectively, thereby achieving an improvement in the overall mechanical properties of the hydrogel.

[0061] See Table 2 for a control group of MXene / BC / PG-AA hydrogels with different BC contents; as can be seen from the table, the BC content gradually increases. When the BC content increases from 4wt% to 8wt%, the tensile strength of the hydrogel gradually increases but the elongation at break decreases. This is because as the BC content increases, its fiber network structure in the hydrogel becomes denser, providing more physical support points for the hydrogel. This strengthening effect enables the hydrogel to better resist deformation when subjected to tension, thereby improving the tensile strength. At high BC content, a certain degree of phase separation may occur in the hydrogel, that is, the interface between the BC nanofibers and the hydrogel matrix becomes discontinuous. This phase separation phenomenon may cause the hydrogel to break easily when subjected to tension, thereby reducing its elongation at break. Therefore, when the BC content continues to increase to 10wt%, the tensile strength and elongation at break of the hydrogel both decrease. The hydrogel has the highest tensile strength (152kPa) when the BC content is 8wt%.

[0062] See Table 3 for a control group of MXene / BC / PG-AA hydrogels with different AA substrate contents; it can be seen from the table that the AA monomer content gradually increases. The increase in the mass proportion of AA monomers means an increase in the chain length in the polymer. Longer molecular chains are more easily stretched when subjected to external forces, thereby better dispersing stress and improving the elongation at break and tensile strength of the hydrogel. When the BC content is 8wt%, the mass proportion of AA monomers in the hydrogel is 27.27wt%, and its elongation at break can reach 720%, while the tensile strength also reaches a relatively high level (153kPa).

[0063] See also Figure 1 The flow chart of the preparation of the MXene / BC / PG-AA conductive hydrogel disclosed in the present invention; as can be seen from the figure, the present invention adopts the "one-pot method" to prepare, the above-mentioned initiator is mixed with the cross-linking agent and the BC solution, and then magnetically stirred for 10 minutes, and then deionized water and MXene single-layer nanosheet solution are added thereto, and finally propylene glycol (PG) and acrylic acid (AA) monomer solutions are dripped. The obtained mixed solution is magnetically stirred at a speed of 800rpm for 20 minutes in an ice water bath. Use a syringe to extract an appropriate amount of the stirred solution, inject it into a homemade vacuum acrylic molding mold (the upper and lower plates are high-temperature resistant acrylic plates, and the middle is a high-temperature resistant molding silica gel plate), seal it and move it into a vacuum drying oven, and polymerize it at 60°C for 4 hours. After cooling to room temperature, demolding can obtain MXene / BC / PG-AA double network conductive hydrogel. The "one-pot method" preparation method is widely used because of its good controllability, high stability and simplicity. The hydrogel prepared by this method not only exhibits high strength and rapid recovery characteristics different from other preparation methods, but also has excellent properties such as high water absorption. In order to study the effect of different cellulose and initiator contents on the performance of hydrogels, hydrogels with different BC and AA contents were prepared by the same process.

[0064] Figure 2The optical performance test diagrams of the various hydrogels disclosed in the present invention; wherein, (a) is a forming mechanism diagram of MXene / BC / PG-AA hydrogel; (b) is a SEM image of the brittle fracture surface of MXene / BC / PG-AA hydrogel; (c) is a Cryo-EM image of the brittle fracture surface of MXene / BC / PG-AA hydrogel; (d) is an XRD diagram of BC, monolayer MXene, BC / PG and MXene / BC / PG-AA hydrogels; (e) is an FTIR spectrum diagram of MXene / BC-AA, BC / PG-AA and MXene / BC / PG-AA hydrogels; it can be seen from the figure that, as shown in Figure (a), ammonium persulfate (APS) is dissolved in water as an initiator in the system and decomposes into two free radicals, namely, sulfacyl radicals and amino radicals. These two free radicals have strong oxidizing and reducing properties, respectively, and can initiate polymerization reactions between acrylic acid (AA) monomers in the solution. In this process, free radicals are continuously generated at the end of the polymer chain and continue to react with the monomers, causing the polymer chain to grow continuously. When the polymer chain grows to a certain length, MBAA begins to play a role as a crosslinker. Its molecule contains two double bonds, which can participate in the polymerization reaction and form crosslinking points. As the crosslinking reaction proceeds, more and more crosslinking points are introduced into the hydrogel network, thereby constructing the three-dimensional network structure of the hydrogel. A large number of hydrophilic functional groups on the surface of the added monolayer TiC2 nanosheets form hydrogen bonds with the water molecules in the above-mentioned gel network, and at the same time form a physical entanglement structure with the long filamentous BC, so that the strength of the prepared gel system is enhanced. In addition, propylene glycol (PG) introduces a large number of hydroxyl groups into the system and forms hydrogen bonds with water molecules again. This leads to an increase in the number of water molecules in the gel and a decrease in the proportion of water loss, thereby forming a more stable system. The cross-sectional SEM image and Cryo-EM image of the hydrogel are shown in Figure (b) and Figure (c), respectively. As can be seen from Figure (b), the MXene conductive material maintains the complete structure of the monolayer in the hydrogel. As can be seen from Figure (c), the uniformly dispersed BC forms a "rigid" support network inside the hydrogel (the part marked with red lines in the figure), making the internal conductive network more stable. This "rigid" support network and the elastic three-dimensional dense honeycomb lattice "flexible" matrix network constructed by AA monomers and PG can work together to form a larger locked crystal lattice, making the hydrogel continuous and stable. The crystalline state of different hydrogels was characterized by XRD, such as Figure 2(d) In the MXene / BC / PG-AA hydrogel, the characteristic peaks of the MXene (2θ=72°) monolayer powder can be clearly observed, indicating that the MXene monolayer nanosheets are uniformly dispersed in the flexible network matrix during the gel preparation process. In the BC / PG hydrogel, only two obvious characteristic peaks (2θ=19.3° and 2θ=36.7°) caused by complex hydrogen bonding and electrostatic interactions can be observed. The formation of hydrogen bonds between BC and other components in the hydrogel changes the crystal structure and chemical environment of BC, thereby affecting the performance of its characteristic peaks in XRD analysis. This also proves its uniform dispersion within the system. In addition, in the MXene / PG / BC hydrogel, the two peaks at the same position become weaker, which is caused by the hydrogen bonding interaction between MXene and PG / BC. Figure 2 (e) FTIR of BC / PG-AA hydrogel. The characteristic peak formed by hydrogen bonding between hydrogel components is located at 3369 cm -1 When MXene is added, the peak associated with the stretching vibrations of the partially overlapping NH and –OH groups becomes stronger and shifts to a relatively lower wavelength of 3335 cm -1 This is due to the formation of more hydrogen bonds between the MXene surface and the AA monomer, and the creation of a large number of hydrogen bonds reduces the force constant of the chemical bonds, resulting in a reduction in the frequency of chemical bond vibration. More importantly, the -OH peak in MXene / BC / PG-AA shifts to 3302 cm -1 , confirming the synergistic effect of monolayer MXene and BC cellulose, which greatly promoted the formation of a dense hydrogel network. In addition, the MXene / BC / PG-AA hydrogel showed a good hydrogel performance at 1696, 1547, 1164, and 1033 cm -1 Characteristic peaks appear at 1693 cm, corresponding to the C=O stretching vibration, NH bending vibration, CO stretching vibration and CN stretching vibration absorption. -1 The stretching vibration of the aromatic ring of the main amide bond (C=O) in the carboxyl group of MXene indicates that MXene forms a complex with the AA monomer through hydrogen bonding. -1 The characteristic absorption peak at 1033 cm indicates the interaction between sulfate anions and hydrogen bonds in MXene / BC-AA hydrogel. -1 The characteristic absorption peak at corresponds to the CO stretching vibration peak of alcohol, indicating that the reagent PG has been successfully introduced into the interior of MXene / BC-AA hydrogel.

[0065] Figure 3The figures are the mechanical property test diagrams of each hydrogel disclosed in the present invention; wherein, (a) is the stretching and weight-bearing test of MXene / BC / PG-AA hydrogel; (b) is the tensile fracture stress-strain curve of hydrogels with different components; (c) is the stress-strain curve of the fracture stretching of MXene / BC / PG-AA hydrogels with different BC contents; (d) is the tensile fracture stress-strain curve of MXene / BC / PG-AA hydrogels with different AA substrate contents; (e) is the stress-strain curve of MXene / BC / PG-AA hydrogels after ten cycles at 300% strain; (f) is the stress test of MXene / BC / PG-AA hydrogels under 1000 stretching cycles; it can be seen from the figure that the mechanical properties of hydrogels are very important for stretchable flexible strain sensors. Figure 3 As shown in (a), the prepared MXene / BC / PG-AA hydrogel exhibits excellent toughness, can withstand 600% tensile strain without any damage, and can be twisted arbitrarily. The hydrogel with a size of 30mm×10mm×1mm can easily lift a 50g weight, and can quickly return to its original state without obvious cracks after removing the weight. In order to verify the effect of different component fillers on the mechanical properties of the hydrogel, the following Figure 3 (b) Comparative tensile test at break. It can be seen that after the introduction of the BC rigid skeleton, the tensile strength of the hydrogel is greatly improved, from 55kPa to 185kPa. After the introduction of PG, although the tensile strength of the hydrogel is slightly reduced (152kPa), its elongation at break is further increased to 862%. This shows that by adding BC and PG to the hydrogel, its tensile strength and elongation at break can be increased respectively, thereby achieving an improvement in the overall mechanical properties of the hydrogel. The contents of BC and AA in the hydrogel respectively affect the performance of the "rigid" support network and the "flexible" matrix network in the hydrogel, thereby affecting the overall mechanical properties of the hydrogel. Figure 3(c) is the tensile stress-strain diagram of hydrogels with different BC contents, and the AA content is controlled to be 25wt% unchanged. When the BC content increases from 4wt% to 8wt%, the tensile strength of the hydrogel gradually increases but the elongation at break decreases. This is because with the increase of BC content, its fiber network structure in the hydrogel becomes more dense, providing more physical support points for the hydrogel. This strengthening effect enables the hydrogel to better resist deformation when subjected to tension, thereby improving the tensile strength. At high BC content, a certain degree of phase separation may occur in the hydrogel, that is, the interface between the BC nanofibers and the hydrogel matrix becomes discontinuous. This phase separation phenomenon may cause the hydrogel to break easily when subjected to tension, thereby reducing its elongation at break. Therefore, when the BC content continues to increase to 10wt%, the tensile strength and elongation at break of the hydrogel both decrease. As can be seen from the figure, the hydrogel has the highest tensile strength (152kPa) when the BC content is 8wt%. Similarly, the increase in the mass proportion of AA monomer means an increase in the chain length in the polymer. Longer molecular chains are more easily stretched when subjected to external forces, thus better dispersing stress and improving the elongation at break and tensile strength of the hydrogel. Figure 3 As shown in (d), when the BC content is 8wt%, the mass proportion of AA monomer in the hydrogel is 27.27wt%, and its elongation at break can reach 720%, while the tensile strength also reaches a relatively high level (153kPa). Figure 3 (e) is the stress-strain curve of MXene / BC / PG-AA hydrogel during 10 cycles of stretching, with a stretching speed of 300 mm / min and a tensile strain of 300%. It can be seen from the stress-strain curve that the hydrogel exhibits hysteresis during the cyclic stretching process, which is caused by the corresponding strain energy dissipation when the hydrogen bonds and ionic coordination bonds in the hydrogel are broken during the stretching process. In addition, the stress-strain curve of the hydrogel in the first cycle is quite different from the curves of the subsequent 9 cycles, while the curves from the second cycle to the tenth cycle are almost overlapping, indicating that the hydrogel material enters a stable stage after energy dissipation in the first cycle. At the same time, from the beginning of unloading, the hydrogel and the fixture completely recover to their original shape in a short time, and the rebound hysteresis time of the hydrogel is very short. This is because after the first stretching cycle, the non-covalent bonds of the polymer network are destroyed, and then a relatively uniform structure is quickly formed. Its internal structure, chain arrangement and response to external stress are relatively stable. The network structure inside the hydrogel can quickly recover to the state before stretching through electrostatic action and coordination bonds, which makes the gel have good rebound properties. The fatigue resistance of stretchable elastomers is also one of the important indicators for evaluating whether the material can withstand continuous work. In order to verify the repeatability of the prepared hydrogel, the MXene / BC / PG-AA hydrogel was stretched to 200% strain and then restored to its original length. The stretch cycle was repeated 1000 times. During the experiment, the stress Figure 3 (f) As shown. The tensile stress of the hydrogel was 44.66 kPa and 44.45 kPa at the 200th and 800th cycles, respectively, with almost no change, indicating that the hydrogel still maintains stable mechanical properties after multiple stretching cycles and has good fatigue resistance. This is because the various reversible bonds in the flexible matrix constructed by AA monomers dynamically break when subjected to load, and quickly reorganize to restore their initial state and tensile strength after the load is removed. It is worth noting that the hydrogen bonds generated by MXene and the BC surface and the locked crystal lattice structure generated by PG and AA monomers ( Figure 2 c) The MXene / BC / PG-AA hydrogel has high tensile strength, large elongation at break and rapid recovery ability, making it suitable for application in flexible strain sensors.

[0066] Figure 4 Figures 1 and 2 are electrical property test diagrams of various hydrogels disclosed in the present invention; wherein, (a) is a schematic diagram of the sensor resistance signal generated by the MXene / BC / PG-AA hydrogel in the circuit; (b) is the conductivity of the MXene / BC / PG-AA hydrogel with different MXene component concentrations; (c) is the change of the resistance strain rate of the MXene / BC / PG-AA hydrogel with the tensile strain; (d) is the response time of the sensor of the MXene / BC / PG-AA hydrogel; (e) is the resistance strain rate of the MXene / BC / PG-AA hydrogel during cyclic tensile strain; (f) is the initial resistance of the MXene / BC / PG-AA hydrogel sensor prepared by the present invention at 20°C to 100°C; it can be seen from the figure that the MXene introduced into the MXene / BC / PG-AA hydrogel interacts with the rigid matrix network through electrostatic effect and weak ion binding, further improving the mechanical properties of the hydrogel, and MXene as a conductive material can also greatly improve the overall conductivity of the hydrogel, making it suitable as a sensitive material for flexible strain sensors. Figure 4 (a) is a schematic diagram of the working of the hydrogel sensor in the circuit. When the hydrogel sensor is subjected to external tensile stress, tensile strain is generated. The spacing between the conductive MXene materials in the hydrogel increases, the conductive path decreases, and the resistance increases significantly. On the contrary, when the hydrogel is compressed, the internal conductive path increases and the resistance decreases. The conductivity of the conductive hydrogel material determines the performance of the strain sensor, and its conductivity increases with the increase of MXene content, such as Figure 4 (c) as shown.

[0067] The sensitivity of the strain sensor can be calculated by formula (1):

[0068]

[0069] Among them, GF is the sensitivity; R is the resistance value of the hydrogel; R0 is the resistance value of the hydrogel before being loaded; ε0 is the normal strain of the sensor.

[0070] The sensitivity of the MXene / BC / PG-AA hydrogel strain sensor prepared in the present invention is as follows: Figure 4 (b) As shown in the figure, the relative change of the sensor resistance value increases linearly with the increase of strain. In the strain range of 0-150%, the GF is 0.36. When the strain increases to 150%-430%, the GF decreases to 0.21. However, when the strain increases to 430%-640%, the GF increases sharply to 1.28. In these three regions, the resistance strain rate has a strong linearity. Its response time and recovery time are both less than 150ms, which is better than most of the previously reported hydrogel sensors such as Figure 4 (d) and Figure 5 . Figure 4 (e) shows the resistance change and stress change of the hydrogel after completing 5 cycles of 100% tensile strain at a rate of 18 mm / min. The output resistance change trend is consistent with the tensile stress, and the output signal is relatively stable, indicating that the prepared MXene / BC / PG-AA hydrogel sensor has excellent stability. Figure 4 (f) is the initial resistance of the hydrogel sensor developed in the present invention at 20-100°C. The temperature in the range of 20-60°C has little effect on the change of its internal resistance value. When the temperature reaches 60°C (polymerization temperature) to 100°C, the sensor resistance value is greatly affected and changes. Therefore, the sensor can work normally under the temperature condition of 20-60°C and is less affected by temperature.

[0071] Figure 5 This is a comparison chart of the comprehensive performance of the MXene / BC / PG-AA hydrogel sensor prepared in the present invention and the sensors in various references; it can be seen from the figure that the hydrogel sensor developed in the present invention has excellent stability and an extremely wide detection range, and is also at a relatively excellent level in terms of the two important indicators of sensitivity and response time.

[0072] Figure 6 A fast-responding, skin-adhesive flexible strain sensor assembled from the MXene / BC / PG-AA hydrogel disclosed in the present invention is used for monitoring a wide range of human motion; wherein, (a) is for detecting finger deformation at different bending angles; (b) is for bending the wrist up and down; (c) is for triceps muscle bulge; (d) is for frowning; and (e) is for swallowing. As can be seen from the figure, the MXene / BC / PG-AA hydrogel designed by the present invention has very high mechanical and sensing properties, and is therefore expected to be applied to strain sensors in the field of physiological signal monitoring. Therefore, the flexible strain sensor is pasted on different parts of the human body for dynamic signal detection of the human body, such as Figure 6 First, the hydrogel sensor was pasted on the finger and wrist joints to measure the joint bending. The sensor was pasted on the second joint of the volunteer's middle finger. When the finger repeatedly stretched and then bent completely (the finger paused at the angles of 135°, 90° and 45°), the corresponding output signal of the sensor was as follows: Figure 6 As shown in (a). As can be seen from the figure, the output signal of the sensor can clearly reflect the movement state of the finger joints. In addition, the up and down bending of the wrist joint is used to analogize the bending of joints in various parts of the body, such as Figure 6 As shown in (b), the electrical signal shows different trends in different bending directions, and the bending direction can be clearly determined. Figure 6 (c) shows that when the volunteer's triceps brachii bulges, its electrical signal changes with the action, with a timely response. When the hydrogel is fixed to the center of the volunteer's eyebrows, it is compressed laterally when the volunteer frowns, and so on. The detected signal is as follows: Figure 6 (d) It still shows similar repetitive electrical signals under smaller compression deformation, which proves that the application of this hydrogel sensor in health monitoring can detect not only larger compression deformation behavior, but also smaller deformation. In addition, it can also detect some subtle movements such as swallowing. The sensor can fully record the vibration generated by the up and down movement of the Adam's apple every time you swallow. Figure 6 (e) In conclusion, the MXene / BC / PG-AA hydrogel sensor prepared by the present invention can not only realize the real-time detection of the subtle strain caused by facial expressions, but also complete the accurate measurement of the large strain caused by joint bending, which provides the possibility for real-time health diagnosis of the human body.

[0073] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a MXene / BC / PG-AA double network conductive hydrogel, characterized in that: include: The initiator and the cross-linking agent are dissolved in the first portion of deionized water, and after the first stirring reaction, the bacterial cellulose solution is added. After the second stirring reaction, the second portion of deionized water and the MXene single-layer nanosheet solution are added, and then the propylene glycol and acrylic acid monomer solution are added. After the third stirring reaction, the mixture is placed in a mold, sealed, subjected to a polymerization reaction, cooled to room temperature, and demolded to obtain a MXene / BC / PG-AA double network conductive hydrogel. The bacterial cellulose solution is prepared by adding deionized water into a bacterial cellulose dispersion; The MXene single-layer nanosheet solution is prepared by dispersing the MXene single-layer nanosheet into deionized water.

2. The method for preparing the MXene / BC / PG-AA double network conductive hydrogel according to claim 1, characterized in that: The dosage ratio of the initiator: cross-linking agent: bacterial cellulose dispersion: MXene monolayer nanosheet: propylene glycol: acrylic acid monomer solution is (200-400) mg: (15-40) mg: (1.5-3) mL: (15-40) mg: (0.8-1.5) mL: (0.4-2) mL.

3. The method for preparing the MXene / BC / PG-AA double network conductive hydrogel according to claim 1, characterized in that: The preparation method of the bacterial cellulose solution comprises: adding 0.5 to 1.5 mL of deionized water to 1.5 to 3 mL of a bacterial cellulose dispersion with a concentration of 200 to 800 mg / mL, and ultrasonically treating the solution for 0.5 to 2 hours until the solution is uniformly mixed to obtain the bacterial cellulose solution.

4. The method for preparing the MXene / BC / PG-AA double network conductive hydrogel according to claim 1, characterized in that: The preparation method of the MXene single-layer nanosheet solution comprises: dispersing 15 to 40 mg of MXene single-layer nanosheets into 1 to 2 mL of deionized water, ultrasonically treating for 0.5 to 2 hours until the dispersion is uniform, and obtaining a MXene single-layer nanosheet solution; the MXene single-layer nanosheet is prepared from single-layer / few-layer Ti3C2 freeze-dried powder.

5. The method for preparing the MXene / BC / PG-AA double network conductive hydrogel according to claim 1, characterized in that: The initiator is ammonium persulfate; the cross-linking agent is N,N'-methylenebisacrylamide.

6. The method for preparing the MXene / BC / PG-AA double network conductive hydrogel according to claim 1, characterized in that: The conditions for the first stirring reaction are: mechanical stirring at 500-1000 rpm for 30-60 min at 55-65°C.

7. The method for preparing the MXene / BC / PG-AA double network conductive hydrogel according to claim 1, characterized in that: The second stirring reaction time is 10 to 25 minutes; the third stirring reaction condition is: magnetic stirring at a speed of 600 to 1000 rpm for 10 to 25 minutes.

8. The method for preparing the MXene / BC / PG-AA double network conductive hydrogel according to claim 1, characterized in that: The polymerization reaction conditions are: polymerization reaction at 55-65° C. for 3-5 hours.

9. The MXene / BC / PG-AA double network conductive hydrogel prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The GF is maintained at 0.3-1.28 within the strain range of 5%-620%, and the response time is 100-150ms; the sensitive performance maintains stable output after 2000 cycles, the tensile stress is 44.66-45.52kPa, the tensile strength is 152-185kPa; the elongation at break is 720%-862%.

10. Application of the MXene / BC / PG-AA double network conductive hydrogel prepared by the preparation method according to any one of claims 1 to 8 in flexible sensors.